Study on" reliability of CTG on fetal outcome at the time of delivery" - Shobanan, P (My University, 2005)
Objective of the study was as certain the reliability of fetal cardiotocography (C.T.G) in predicting baby's condition at birth. It is a Descriptive observational study to find out the reliability of fetal cardiotocography in predicting baby's condition at birth. The study was carried out at Ward 3,5,15 and 16 De Soysa Maternity Hospital and Ward 25 N.C.T.H. 1246 pregnant mothers between the P.O.A of 37 to 41 weeks were included in this study. Babies were considered having fetal distress l)when Apgar score 7 at 5mts of birth2)when baby needed I.P.P. V soon after birth3)when presence of moderate or thick meconium at the onset of labour4)When appearance of meconium during labourOveral1 sensitivity of C.T.G for an abdominal tracing is 57.6 percent (sensitivity of CTG for an abnormal tracing High risk mother is 58.4 percent, in a Low risk mothers it is 40 percent).Overall specifically ,of C.T.G for abnormal tracing is 90.5 percent (specificity of CTG for abnormal tracing High risk mother is- 92.6 percent, in a Low risk mother it is-81.9 percent) Positive predict value of CTG is 45.7 percent Negative predictive value of CTG is 93.9 percent. This study shows C.T.G has a high incidence of false positive and low incidence of false negative Although C. T. G has a low sensitivity it is relatively more sensitive to high risk cases. These findings suggest that the current overdependence on fetal monitoring by-C.T.G alone should be examined and that other reliable indicators should be sought.